Investigation of lectin activity in Theileria annulata piroplasms - Kaynar, Ö; Güldür, T; Karapinar, T (Akademiai Kiado Zrt, 2005)
Adhesion to target cells is an essential step in the pathogenesis of many protozoal infections. Some protozoa have been reported to have a lectin activity involved in their attachment to the cell surface. The ligand-receptor interaction involved in Theileria annulata infection is unclear at present, in spite of the fact that some aspects of the process have been investigated. To this end, T annulata piroplasms have been screened for lectin activity. Blood taken from infected cattle was first depleted of leukocytes and then subjected to ammonium chloride lysis in order to isolate the piroplasms. The piroplasms were homogenised and a crude membrane extract was prepared by centrifugation. To investigate lectin activity in piroplasm proteins, a simple screening procedure was employed for analysing piroplasm proteins binding to various lectin ligands. Numerous immobilised lectin ligands (L-fucose-sepharose, N-acetyl-neuraminic acid-sepharose, N-acetyl-D-galactosamine-agarose, N-acetyl-D-glucosamine-agarose, D-mannose-agarose, beta-D-glucose-agarose, a-methyl-D-mannoside-agarose) were incubated with T annulata piroplasm crude membrane extract. The ligand-bound proteins were eluted and separated by a brief centrifugation and determined by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE). The present study suggests that a 32 kDa protein of piroplasm binds to D-galactosyl residues of the agarose matrix and that the binding is inhibited by galactose and not by the other monosaccharides tested.
Keywords: Theileria annulata; piroplasm; gal-lectin